Valoración medicolegal de la infección por COVID-19 en el ámbito laboral - Martí-Amengual, Gabriel (Revista Espan~ola De Medicina Legal, 2020)
Spain is one of the countries most affected by the COVID-19 pandemic. To date, 22% of reported cases are healthcare professionals, and 76% of them are women. Given that many healthcare professionals may have been infected in their workplace, we have reviewed the occupational health challenges posed by COVID-19. The Spanish laws and the recommendations of the International Labor Organization are described. The review covers the classification of SARS-CoV-2 as a biological agent in group 3 and of COVID-19 as an occupational accident or disease, its repercussions in temporary and permanent disabilities, sequelae and death, and the possible claims of those who may have developed the disease due to the lack of preventive measures.